On the variability of atmospheric 222Rn activity concentrations measured at Neumayer, coastal Antarctica - Weller, Rolf; Levin, Ingeborg; Schmithüsen, Dominik; Nachbar, Mario; Asseng, J.; Wagenbach, Dietmar (Atmospheric chemistry and physics, 2014)
Abstract. We report on continuously measured 222Rn activity concentrations in near-surface air at Neumayer Station in the period 1995-2011. This 17-year record showed no long-term trend and has overall mean ± standard deviation of (0.019 ± 0.012) Bq m-3. A distinct and persistent seasonality could be distinguished with maximum values of (0.028 ± 0.013) Bq m-3 from January to March and minimum values of (0.015 ± 0.009) Bq m-3 from May to October. Elevated 222Rn activity concentrations were typically associated with air mass transport from the Antarctic Plateau. Our results do not support a relation between enhanced 222Rn activity concentrations at Neumayer and cyclonic activity or long-range transport from South America. The impact of oceanic 222Rn emissions could not be properly assessed but we tentatively identified regional sea ice extent (SIE) variability as a significant driver of the annual 222Rn cycle.>